Potential of Duckweed (Lemna minor) for the Phytoremediation of Landfill Leachate - M. K. Daud; Shafaqat Ali; Zohaib Abbas; Ihsan Elahi Zaheer; Muhammad Ahsan Riaz; Afifa Malik; Afzal Hussain; Muhammad Rizwan; Muhammad Zia-ur-Rehman; Shui Jin Zhu (Journal of Chemistry)
Phytoextraction of zinc, copper, lead, iron, and nickel from landfill leachate by duckweed (L. minor) was investigated every 3 days over a period of 2 weeks. Bioconcentration factor and removal efficiency were also calculated. Results of this study proved that L. minor significantly reduced the concentration of heavy metals in landfill leachate. Removal efficiency of L. minor, for all the metals, from landfill leachate was more than 70% with the maximum value for copper (91%). Reduction in chemical oxygen demand (COD) and biological oxygen demand (BOD) was observed by 39% and 47%, respectively. However, other physiochemical parameters like pH, total suspended solids, (TSS) and total dissolved solids (TDS) were reduced by 13%, 33%, and 41%, respectively. The value of bioconcentration factor (BCF) was less than 1 with the maximum figure for copper (0.84) and lead (0.81), showing that the plant is a moderate accumulator for these heavy metals. Duckweed (L. minor) appeared as a sustainable alternative candidate and is recommended for the treatment of landfill leachate waste water contaminants.